Cameroon : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper on Cameroon identifies impediments to growth acceleration in the country. A two-step approach is followed: first, the characteristics of middle-income countries currently experiencing growth accelerations are examined; and, second, the extent to which Cameroon shares these characteristics is assessed. The focus of the analysis is a set of variables the literature has identified as helping to accelerate growth. This paper also presents a possible fiscal strategy for Cameroon based on the permanent income approach.